Environmental conditions, subsidiaries' autonomy and global innovation in multinational enterprises. Issue 2 (21st February 2020) - Pereira, Rafael Morais; Borini, Felipe Mendes; Santos, Leandro Lima; Oliveira Jr, Moacir de Miranda
Abstract : Purpose: The purpose of this study is to analyze the influence of environmental conditions of the subsidiaries' host country in the process of developing global innovation. It is argued that, even though the local environment in which subsidiaries are placed must be taken into account, this is not the only important factor to directly create global innovation, but it also becomes necessary for the subsidiaries to be endowed with autonomy, in this sense allowing them to enjoy the local conditions for innovation purposes. Design/methodology/approach: A quantitative approach is opted for the research development, while the hypotheses were evaluated from the analysis of the relationship between four constructs: global innovation, local market conditions, local competitive dynamics and autonomy to innovate. The structural equation modeling technique is applied, using data from 172 foreign subsidiaries located in Brazil. Findings: The validity and reliability parameters analyzed in the proposed model were suitable (average variance extracted, Cronbach's alpha, composite reliability and discriminant validity). H1 (the better the market conditions of the host country, the greater the subsidiary's autonomy to innovate) was not supported. However, both H2 and H3 were supported, suggesting the influence of local competitive dynamics on autonomy to innovate, and also the influence of autonomy to innovate on global innovation, respectively. Originality/value: This paper provides some contributions for the advance in researches about the global innovation management, considering the subsidiaries' perspective, showing the relevance of the subsidiary's autonomy for the development of global innovation given a favorable local competitive dynamic.